2015
DOI: 10.4236/ojvm.2015.58025
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Influencing Haematological, Serum and Bio-Chemical References in Livestock Animals under Different Management Systems

Abstract: Serum biochemical and haematological indices constitute important panels in the diagnosis, prognosis and treatment of livestock diseases via the investigations of myriads of parameters influencing these blood and serum biochemical indices. Serum biochemical indices, haematological indices and blood electrolytes are critical physiological indices which have health implications on the diagnosis, prognosis and treatment of livestock diseases especially in animals bred under different management systems. It is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 31 publications
5
34
0
Order By: Relevance
“…Haematology and serum biochemistry assay of livestock determines the physiological disposition of the animals to their nutrition (Menon et al 2013). Deficiency of both macro-and micro-nutrients triggers enormous discrepancies in haematological and serum biochemical profiles of livestock animals (Onasanya et al 2015). Data in the present study has clearly demonstrated that changes in nutritional quality in the pasture had an impact on blood haematological profile, and such a trend had also been reported by Šoch et al (2011).…”
Section: Discussionsupporting
confidence: 85%
“…Haematology and serum biochemistry assay of livestock determines the physiological disposition of the animals to their nutrition (Menon et al 2013). Deficiency of both macro-and micro-nutrients triggers enormous discrepancies in haematological and serum biochemical profiles of livestock animals (Onasanya et al 2015). Data in the present study has clearly demonstrated that changes in nutritional quality in the pasture had an impact on blood haematological profile, and such a trend had also been reported by Šoch et al (2011).…”
Section: Discussionsupporting
confidence: 85%
“…Glucose concentration during the experimental period was 55.42±3.47 mg/ml. This result was compatible with (27) in Yankasa sheep (54.05 ±1.88 mg/ml) while it was higher than (28) in Awassi rams (46.12±1.01 mg/ml) and (27) in Ouda and Balami rams (45.04±1.09 and 37.83±2.1 mg/ml respectively), this difference may be due to breed effect (29) or the nature of nutrition and management (30). seasonal fluctuations of glucose concentration in rams were observed (table 2), the highest concentration was recorded in winter and autumn (81.8±3.753 and 68.7±2.381 mg/ml respectively) and significantly (P≤0.05) decreased in spring and summer (34.8±1.652 and 36.4±1.529 mg/ml respectively), similar results were observed by (31) and this rise in glucose level in winter may be related to inhibition of insulin secretion due to the low nutrition because cold stress (32).…”
Section: Table (1) Total the Scrotal Circumference Body Condition Scsupporting
confidence: 86%
“…Many factors may influence the hematological and biochemical blood parameters, these factors divide into two kinds: 1) genetic factors including genotype and breed. 2): environmental factors, including age, sex, species, season, nutrition, geographic location and physiological status (Kassim and AL-Hellou 2018;Onasanya et al 2015;Njidda et al 2014;Prisacaru 2014;Yokus et al 2006;Nazifi et al 2003).…”
Section: Introductionmentioning
confidence: 99%